Intraocular Pressure Control and Post Operative Complications with Mitomycin ? C Augmented Trabeculectomy in Primary Open Angle and Primary Angle-Closure Glaucoma - Dilshad A Laghari, P. S Mahar (Pakistan Journal of Ophthalmology, 2011)
Purpose: To compare intraocular pressure (IOP) control and post operative complications after trabeculectomy with Mitomycin-C (MMC) in patients with primary open angle glaucoma (POAG) and primary angle-closure glaucoma (PACG). Material and Methods: Sixty patients of both genders with age range of 40 to 70 years, fulfilling the inclusion criteria were planned for trabeculectomy. The patients were selected from glaucoma clinic who were diagnosed as having POAG or PACG with uncontrolled IOP (more than 22mmHg) with topical anti glaucoma medication. Thirty patients (30 eyes) were randomly enrolled in each group. The patient’s IOP was assed at all post operative follow up visits i.e. at day 1, 1 week, 1 month, 6 months and 1 year with record of post operative complications. Results: The mean IOP in POAG patients, preoperatively was measured at 22.93 + 3.9 mmHg. There was a mean drop of 10.63 ± 3.2 mm Hg at 12 months post operatively. The mean IOP in PACG group, registered at 22.13 SD ± 7.44 mmHg preoperatively. After surgery, mean IOP dropped to 9.42 ± 2.1mm Hg (Please check this figure) at 12 months follow up. There was insignificant difference between post operative IOPs at different follow ups in both POAG and PACG patients with p-value = 0.092 and 0.34 respectively. In early post operative phase, out of 30 patients, 18 (60%) had complications in PACG group and 9 (30%) patients had complications in POAG group (p-value= 0.0379). In late post operative phase, 8 patients (26.6%) had complications with PACG and only 1 (3.3%) patient showed complication in POAG group (p-value=0.0301). Conclusion: MMC augmented trabeculectomy was beneficial in patients with POAG and PACG with similar control of IOP, although range of complications were on the high side in PACG group but statistically this was found insignificant (p-value=0.0301)